Proceedings of the 8th Workshop on Social Network Mining and Analysis 2014
DOI: 10.1145/2659480.2659498
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cross-site Linking in Online Social Networks

Abstract: Online social networks (OSNs) have attracted billions of users, and play an important role in people's daily life. A user often has accounts on multiple OSN sites. In this paper, we study the emerging "cross-site linking" function, which is supported by many OSNs. Our study is based on Foursquare, a representative location-based social networking (LBSN) service. We conduct a data-driven analysis by using crawled public profiles of almost all (if not all) Foursquare users. Our analysis has shown that the crosss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 20 publications
(19 reference statements)
0
25
0
Order By: Relevance
“…The authors observed that active Foursquare users are usually active in Twitter as well, which is consistent with the observations derived from our dataset. In other study, Chen et al [4] tried to discover cross-site linking regularities in largescale online social networks dataset. By gathering almost all Foursquare user network graph and applying first order statistical analysis, the authors [4] were able to extract comprehensive knowledge about the Foursquare network structure and users cross social network behaviour.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors observed that active Foursquare users are usually active in Twitter as well, which is consistent with the observations derived from our dataset. In other study, Chen et al [4] tried to discover cross-site linking regularities in largescale online social networks dataset. By gathering almost all Foursquare user network graph and applying first order statistical analysis, the authors [4] were able to extract comprehensive knowledge about the Foursquare network structure and users cross social network behaviour.…”
Section: Related Workmentioning
confidence: 99%
“…In other study, Chen et al [4] tried to discover cross-site linking regularities in largescale online social networks dataset. By gathering almost all Foursquare user network graph and applying first order statistical analysis, the authors [4] were able to extract comprehensive knowledge about the Foursquare network structure and users cross social network behaviour. At the same time, Zhong et al [29] attempted to discover network evolution relations across various social forums datasets (Tencent, Epinion, Facebook, Xiaonei, Twitter, Sina Weibo, Github, StackOverflow).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This is often a mandatory step for users to perform cross-posting. Chen et al, using a data-driven approach, investigated how users cross-linked their Foursquare accounts to other OSNs, namely Facebook and Twitter [14]. Most relevant to cross-posting is work by Ottoni et al [15].…”
Section: Related Workmentioning
confidence: 99%
“…Numerous online social networks (OSNs) have emerged in recent years. Many of them, such as Foursquare, Pinterest, Quora and Medium, have enabled the cross-site linking function [1]. This function allows a user to link her account on one OSN to her accounts on other OSNs.…”
Section: Introductionmentioning
confidence: 99%